اليوتيوب كوسيلة لتعليم اللغة العربية - Faizati, Farah; Aisyah, Aisyah; Husniyah, Husniyah; Mahridawati, Mahridawati (STIT Darul Hijrah Martapura, 2024)
ABSTRACTThe world of education, especially the process of learning like Arabic, has changed a lot due to technology development and globalization. YouTube, as one of the most popular video-sharing platforms, provides a variety of educational content that could benefit both teachers and students in Arabic language learning. This study aims to characterize the advantages of YouTube as a media for learning Arabic, describe strategies for its usability and usage, and address problems experienced by teachers and learners in making use of YouTube. This study is descriptive qualitative research by reviewing literature and analyzing findings of studies associated with using YouTube as an Arabic language learning media. The results show that YouTube, besides providing information, establishes a pleasant studying atmosphere. Video as an audio-visual medium on YouTube can enhance comprehension and offer a better, more enjoyable learning experience. Learning has become more accessible, though challenges such as content relevance and video quality must be addressed for effective learning. YouTube can be an innovative and effective media for teaching Arabic with the right approach.Keyword: educational media; Youtube; Arabic language مستخلص البحثتطور التكنولوجيا والعولمة أحدث تغييرات مهمة في عالم التعليم، وخاصة في عملية التعلم، بما في ذلك تعلم اللغة العربية. يوتيوب، كأحد أكثر منصات مشاركة الفيديو شهرة، يقدم مجموعة متنوعة من المحتويات التعليمية التي يمكن أن يستفيد منها المعلمون والطلاب في تعليم اللغة العربية. هذه الدراسة تهدف إلى وصف فوائد يوتيوب كوسيلة لتعلم اللغة العربية، وشرح استراتيجيات استخدامه، بالإضافة إلى التحديات التي يواجهها المعلمون والطلاب عند استخدامه. نوع البحث المستخدم هو البحث الوصفي النوعي، مع استخدام دراسة مكتبة لمراجعة نتائج الأبحاث المتعلقة باستخدام يوتيوب كوسيلة لتعلم اللغة العربية. تشير نتائج البحث إلى أن يوتيوب لا يسهل فقط الوصول إلى المعلومات، بل يخلق أيضًا بيئة تعلم ممتعة. استخدام الوسائط السمعية والبصرية على يوتيوب يمكن أن يعزز فهم المواد الدراسية ويغني تجربة التعلم بشكل أكثر جاذبية ومتعة. ومع ذلك، تبقى التحديات مثل ملاءمة المحتوى وجودة الفيديو بحاجة إلى الاعتبار لضمان فعالية التعلم. مع النهج الصحيح، يمكن أن يصبح يوتيوب وسيلة مبتكرة وفعالة لتعليم اللغة العربية.الكلمات المفتاحية: وسائل التعليم، يوتيوب، اللغة العربية.